Sexting experiences and motivations among adolescents with ADHD and ASD. (March 2023) - Lunde, Carolina; Burén, Jonas; Reinholdsson, Tommy; Daneback, Kristian
Abstract: Sexting (i.e., to send and receive self-produced sexual materials) has become a common element in adolescents' socio-sexual exploration. Although often harmless, sexting also involves the risk of abuse, and potentially more so for some adolescents than for others. Adolescents with attention deficit disorder (ADHD) and/or autism spectrum disorder (ASD) have been pointed out as potentially more vulnerable online, yet research to support or reject these concerns is sparse. Focusing on sending sexts, this study compares sexting rates, sexting experiences, and sexting motivations of Swedish adolescents with ADHD and/or ASD to adolescents without these diagnoses. In all, 1063 adolescents (aged 15 to 19), 164 of whom self-reported ADHD and/or ASD, completed a survey about their sexting experiences. The results revealed both differences and similarities between groups. Adolescents with ADHD sexted more and reported more pressure to sext. No group differences were noted in terms of reporting positive or negative experiences. Sexting motivations were also similar between groups, although sexting for aggravated reasons was more common among adolescents with ADHD and/or ASD. Our findings suggest that adolescents with ADHD and ASD mainly use sexting for sexual gratification and exploration, but also report experiences and motivations that may indicate increased vulnerability in relation to sexting. Highlights: Adolescents, including those with ADHD/ASD, mainly use sexting for sexual gratification and exploration. Adolescents with ADHD sexted more and reported feeling more pressure to engage in sexting. Sexting for aggravated reasons was more common among adolescents with ADHD and/or ASD.